Assessment of Copyright Law in Journalism Practice in Nigeria - Nyitse, Gabriel T.; Inja, Ndernen (European Journal of Applied Sciences, 2022)
The right to protect one’s intellectual property overtime has increasingly become pertinent given credence to our day to day activities in our modern age. Hence, it is essential that people’s mental efforts which are often seen or recognized in the society should be protected from piracy and plagiarism. This paper is positioned to examine how copyright law is used to check replication of peoples work without their permission and to encourage originality of intellectual property produced both in private sectors and in the journalism practice. The paper thus, made laudable findings. This right, however, does not bestow on the copyright owner monopoly to control access to copyrighted materials. This paper discusses copyright law and journalism as its key concepts. The study on the illegal practices of copyrighted work as damaging to the rights of owners of copyrighted materials as it stifles creativity, innovation and growth, and the summary of the Laws guiding copyright materials and aimed at balancing the exclusive rights of copyright owners and access to information by all, in order not to harm researchers, and erudite. The paper suggests that there is need to raise awareness about copyright law in journalism practice in order to discourage violations, thereby robbing copyrighted owners of the benefit of their labour.